DNA fragmentation and chromatin denaturation in various sperm categories: A prospective cohort study - Maroua Ben Rhouma; Hatem Bahri; Mustapha Ben Khalifa; Mohsen Sakly; Khemais Ben Rhouma; Moncef Benkhalifa; Olfa Tebourbi (Asian Pacific Journal of Reproduction, 2025)
Objective: To evaluate how DNA fragmentation index (DFT) and chromatin denaturation index (CDI) relate to semen parameters across different types of male infertility, thereby improving the understanding and assessment of sperm quality. Methods: A prospective and descriptive cohort study was conducted over two years at the Integrated Physiology Laboratory of the University of Carthage in collaboration with the Alyssa Fertility Group, Tunisia. A total of 163 participants were classified into five groups based on their semen parameters: normozoospermia, oligozoospermia, asthenozoospermia, teratozoospermia, and oligo-astheno-teratozoospermia. The normozoospermia group was selected from volunteers who had children. Semen samples were analyzed according to WHO guidelines. DFI was measured using Halosperm® and CDI was tested using aniline blue staining. Results: Both DFI and CDI were significantly higher in all infertility groups, with the oligozoospermia group showing the highest DFI and CDI. Negative correlations were found between DFI/CDI and sperm motility, concentration, and morphology in the affected groups. The normozoospermia group served as a control with the lowest DFI and CDI values. Conclusions: DFI and CDI are increasingly recognized as important biomarkers for evaluating sperm quality in cases of male infertility. Their elevated levels in patients with oligozoospermia, asthenozoospermia, teratozoospermia, and oligo-astheno-teratozoospermia underscore their potential role in not only diagnosing male infertility but also in assessing the overall reproductive outcomes for affected individuals, thus guiding more effective treatment strategies.